Les interactions entre formation et innovation au Royaume-Uni au tournant du XXIe siècle - Catherine Coron (Revue LISA)
One of the main features of economic activity in the United Kingdom is the diffusion of innovation which creates greater needs in the fields of labour training and education. This paper tries to analyse the system which has linked training and education with R&D and innovation since the 1990s. First, young people are showing a growing interest in training in new technologies, perhaps because they have become aware that they have to, if they want to keep up with the increased pace of innovation. Besides, public investment in training has been declining since 1995 and its level is too low to enable the labour force to benefit from innovation. This explains why we can find, on the one hand, a strong demand for training coming from individuals and, on the other hand, an insufficient supply from the State. The situation looks paradoxical because the government is aware of the fact that training has become an economic issue while trying to minimize the effects of its financial disengagement policy, which started in the 1990s, by opting for a growing interventionist policy. Hence, in spite of successive governments’ huge efforts to overcome the country’s difficulties in education, the training level of a great part of the labour force remains inadequate and curbs the appropriation and diffusion of innovation.